Inheritance of Resistance to Stalk Rot in Cauliflower (Brassica oleracea var. botrytis L.) - Singh Thakur, Bhupinder (International Journal of Bio-resource and Stress Management, 2023)
Germplasm of late group cauliflower was screened under artificially inoculated conditions for resistance to stalk rot. This screening of the available germplasm revealed that Janavon and RSK 1301 were the genotypes resistant to stalk rot. These resistant genotypes were selected as parents for making crosses with the common high yielding susceptible varieties. Therefore crosses between susceptible PSB1 (commercial variety) and KJ 47 (elite line) and resistant parents (Janavon and RSK 1301) were attempted to work out the inheritance pattern of the disease resistance. All the F1’s of susceptible×resistant parents with mean disease incidence of 60.67 to 71.19% were found to be susceptible to stalk rot disease. As resistance was not shown by any of the F1’s, therefore it was clear that the genes responsible for resistance could not express themselves. The disease reaction recorded in the F1’s revealed that resistance to stalk rot was recessive to susceptibility. The intermediate disease reaction in the F2 generation and low disease reaction in the back cross generations indicated that resistance to stalk rot is polygenic in nature. Additive effect of the genes was evident from the Generation means analysis revealed pronounced effect of additivity of genes in inheritance of the resistance to stalk rot.